Structure-Property Relationship for Different Mesoporous Silica Nanoparticles and its Drug Delivery Applications: A Review - Kazemzadeh, Parya; Sayadi, Khalil; Toolabi, Ali; Sayadi, Jalil; Zeraati, Malihe; Chauhan, Narendra Pal Singh; Sargazi, Ghasem (Frontiers in Chemistry, 2022)
Mesoporous silica nanoparticles (MSNs) are widely used as a promising candidate for drug delivery applications due to silica's favorable biocompatibility, thermal stability, and chemical properties. Silica's unique mesoporous structure allows for effective drug loading and controlled release at the target site. In this review, we have discussed various methods of MSNs, mechanism, properties and its drug delivery applications of MSNs. As a result, we came to the conclusion that more in vivo biocompatibility studies, toxicity studies, bio-distribution studies and clinical research are essential for MSN advancement.